Plant growth promoting microbes: Diverse roles for sustainable and ecofriendly agriculture - Mahesh Kumar; Poonam; Shamshad Ahmad; R.P. Singh (Energy Nexus, 2022)
With increasing population and depleting natural resources there is a need for increasing agricultural productivity in sustainable and ecofriendly manner. The conventional agricultural practices utilize a lot of chemical fertilizers for increasing the productivity that pose a threat to agro-ecosystems like food chain contamination, soil quality degradation, water pollution etc. To overcome all these problems, there is need to shift towards sustainable agricultural practices like application of Plant Growth Promoting Microbes (PGPMs) instead of conventional chemical fertilizers restoring the agro-ecosystems. These microbes live in soil and are associated with rhizospheric region of plants, where they stimulate growth and productivity of their hosts by different direct and indirect mechanisms e.g. by phytohormones, siderophores, solubilization of minerals etc. Microbes used to make available soil nutrient to crops without compromising with the soil fertility in environmentally sustainable manner. Previous studies have shown positive effects of microbes on growth and yield of various crops in different climatic conditions, soil types also under biotic and abiotic stress conditions. Further, these microbes have also been used successfully as bio-control agents for various pathogens in the plants. Present review presents an overview of different mechanisms used by these microbes as growth promoter and role performed as bio-control agents for enhancing the productivity as well as the supportive role played for sustainable and ecofriendly agriculture without causing any negative effects on the environment and on living beings health.